Relevance of Chronic Total Occlusion for Outcome of Ventricular Tachycardia Ablation in Ischemic Cardiomyopathy - Julia Anna Lurz; Eileen Schmidt; Karl-Patrik Kresoja; Federica Torri; Sebastian König; Angeliki Darma; Arash Arya; Livio Bertagnolli; Gerhard Hindricks; Borislav Dinov (Journal of Interventional Cardiology)
Background. Catheter ablation of ventricular tachycardia (VT) in patients with ischemic cardiomyopathy (ICM) is an effective tool to prevent VT recurrences. Chronic total occlusion (CTO) represents a clinically relevant entity in ICM patients and is an independent predictor of ventricular arrhythmia and mortality. The effects of CTO on the outcome of VT ablation are not well-studied. Objective. This analysis aimed to identify the impact of CTO, revascularized, or not revascularized, on the outcome of VT ablation. Methods and Results. Of 385 consecutive subjects with ICM-VT who underwent catheter VT ablation for monomorphic VT at Heart Center Leipzig between 2008 and 2017, 108 patients without CTO and 191 patients with CTO were included in the analysis. Within a median follow-up time of 557 days (IQR 149, 1095), VT recurred in 77 (40%) patients in the CTO and 40 (37.0%) in the non-CTO cohort (p=0.62). In a multivariable model, a 10% stepwise change in LVEF as well as ICD on admission was associated with VT recurrence (HRadj 1.82, 95% CI 1.04–3.18 and HRadj 1.35, 95% CI 1.23–1.61, respectively). Of the CTO cohort before ablation, 45% had received revascularization, which was independently associated with a higher risk for VT recurrence (HR 2.12, 95% CI 1.35–3.34) as compared to nonrevascularized CTO. Conclusion. In ICM patients with and without CTO, VT ablation was associated with equal effectiveness with regard to VT recurrence. However, in revascularized CTO patients, the risk of recurrence of VT after ablation was significantly increased.